Reconstruction of Nusyuz in the Compilation of Islamic Law from the Perspectives of Qira'ah Mubadalah and Rawls’s Theory of Justice - Achmad Kadarisman; Saifullah Saifullah; Erfaniah Zuhriah; Abd Rouf; Abdul Hakim (Hukum Keluarga Islam IAIN LANGSA, 2025)
The Compilation of Islamic Law in Indonesia gives the impression of marginalizing wives and does not regulate the possibility of nusyuz committed by husbands. The existing nusyuz norms in Indonesia still reflect gender dominance, which is contrary to the principles of justice and equality increasingly emphasized in modern society. This research seeks to address the legal gap by reconstructing the nusyuz norms in Articles 80, 84, and 149 of the Compilation of Islamic Law, drawing on the concept of Qiraah Mubadalah and John Rawls's theory of justice. This study employs legal research using legislative, historical, conceptual, case, and comparative approaches, with qualitative methods for analyzing legal materials. The findings reveal that the current nusyuz norms in the Compilation of Islamic Law still contain patriarchal bias and fail to fully realize the principle of relational justice. From the perspective of Qiraah Mubadalah, both husbands and wives have the potential to commit nusyuz, thus requiring fair legal treatment. The reconstruction of these norms should affirm the importance of reciprocity (mubadalah) in marital relationships, in which husbands and wives are not positioned hierarchically but as equal partners who fairly fulfill each other’s rights and obligations. Meanwhile, Rawls’s theory of justice suggests that legal norms should be drafted without gender bias, ensuring justice for all parties, particularly those in vulnerable positions. Therefore, the reconstructed nusyuz norms must recognize the mutual rights and obligations of both husband and wife in a fair and equal manner.